ANALISIS KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN KUBU RAYA PADA TAHUN 2012-2015 - Molita, Tia B1031131020 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Accounting has a major role in preparing financial statements as a form of implementation in public accountability and is also a means of measuring performance in local government to manage its regional finances through the analysis of financial ratios and realization reports to the Kubu District Government's Revenue and Expenditure Budget (APBD) The Kingdom has been implemented.The purpose of this paper is to know the ratio contained in the report on realization of local government budget Kubu Raya. The method of this research is descriptive method that is method which use problem solving procedure which can be investigated by describing condition happened at institution, society, and so on. The result of this study is the financial performance obtained through the ratio of the APBD realization report is not good, because the ratio of the regional income to the lack of income from the community, and also the regional spending has a lack of grant funds for community organizations, although sometimes income and expenditure also experienced Increase.Â Keywords: Financial Performance, Income Budget, Budget Expenditure,